United States, man standing on dead walrus off shore in Utqiaġvik - Sorensen, Clarence Woodrow, 1907-1982; Harris, Eugene V., 1913-1978 (1959)
Barrow 94. Waterfront at Point Barrow, Alaska Man standing on Walrus carcass at waterfront. Grayscale Sorensen Safety Negatives, Binder: North & Central America 3